Digital Simulation as a Design Method of Artificial Lighting for Prayer Rooms - Ola, Frengky Benediktus; Michelle, Brigitta (Program Studi Sistem Informasi Universitas Atma Jaya Yogyakarta, 2021)
This article aims to describe the results of the lighting design for the prayer room using a simulation method to answer the needs of function and ambience. In general, the lighting design for prayer rooms does not use an integrated approach. A common problem faced by prayer rooms, especially churches and chapels, is too glaring or too dim in some cases. The results of the community service activities in the form of lighting planning for the Church of Santa Theresia Sedayu and Chapel of SMA de Britto with the digital simulation method expect to provide an overview of designing lighting with a more measured method that can meet the needs of the ambience. Lighting simulation in both cases uses DIALux Evo software. The simulation result shows that the lighting design meets lighting standards and is able to provide a sacred atmosphere. Concerning the study, solving lighting problems with the digital simulation as the method is more scalable and can meet the ambience needs. Field measurements of the lighting design results can be carried out in the future to measure the simulation's level of achievement and validation.